PENGARUH PEMBERIAN VITAMIN C DAN SULFAS FERROSES (SF) PADA IBU HAMIL UNTUK MENGURANGI RISIKO ANEMIA PADA SAAT PERSALINAN MENGGUNAKAN ANALISIS DATA BERPASANGAN (STUDI KASUS SEBUAH KLINIK BERSALIN DI BANJARMASIN) - Dewi Anggraini; Dewi Sri Susanti; Nur Salam (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2011)
Paired data analysis (analysis of paired data) is a statistical analysis that is used for a studywhere there is only one sample or group of individuals or objects of observation are used andsubjected to two treatments or measurements resulting in a valuepairs. Two pieces of data said tobe in pairs when any value in the first data in accordance and is associated with a single value toboth the data. In other words, two pairs of data which can be interpreted as a sample of thesubject/object of the same observations are given two treatments (treatment)/differentmeasurements. This study aims to clarify the effect of Vitamin C and Sulfas Ferroses (SF) inpregnant women towards the increasing level of their hemoglobin.The method of this research is a study literature and case study, by collecting and studyng therelevant references on the analysis of data pairs, then applying to data in a maternity clinic inBanjarmasin.The results shows that Vitamin C and Sulfas Ferroses (SF) have influenced to the increase ofhemoglobin level in pregnant women.